2010
DOI: 10.1021/ct100398m
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of 57Fe Mössbauer Parameters by Density Functional Theory: A Benchmark Study

Abstract: We report the performance of eight density functionals (B3LYP, BPW91, OLYP, O3LYP, M06, M06-2X, PBE, and SVWN5) in two Gaussian basis sets (Wachters and Partridge-1 on iron atoms; cc-pVDZ on the rest of atoms) for the prediction of the isomer shift (IS) and the quadrupole splitting (QS) parameters of Mössbauer spectroscopy. Two sources of geometry (density functional theory-optimized and X-ray) are used. Our data set consists of 31 iron-containing compounds (35 signals), the Mössbauer spectra of which were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
130
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(141 citation statements)
references
References 115 publications
(283 reference statements)
9
130
0
Order By: Relevance
“…Hence the isomer shift is linearly proportional to the electron density at the indicator nucleus. In recent years this conclusion is confirmed by results of DFT calculations of the electron density at the nuclei 57 Fe [49,52], 119 Sn [43], 121 Sb [43,44], 127 I [45], and 197 Au [51].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Hence the isomer shift is linearly proportional to the electron density at the indicator nucleus. In recent years this conclusion is confirmed by results of DFT calculations of the electron density at the nuclei 57 Fe [49,52], 119 Sn [43], 121 Sb [43,44], 127 I [45], and 197 Au [51].…”
Section: Introductionmentioning
confidence: 73%
“…We mention in passing that the D value obtained for 57 Fe [49,52], 119 Sn [47,48], 121 Sb [44], and 127 I [45] [53,54] and are at the basis of the correlation analysis. Therefore this investigative techniques are promising in understanding the mechanism for the influence of substituents on the d and D parameters.…”
Section: Introductionmentioning
confidence: 99%
“…40 The B3LYP functional was used to compute the isomer shift whereas O3LYP was the functional of choice for the quadrupole splitting parameter. The completely uncontracted Partridge-1 basis set was placed on the iron atoms, and the conventional cc-pVDZ basis resided on the rest of atoms of the model.…”
Section: Computation Detailsmentioning
confidence: 99%
“…3,1726 For example, Neese and coworkers have found that fit parameters are relatively insensitive to whether nonrelativistic or quasi-relativistic (via the zero-order regular approximation, ZORA) DFT methods are employed. 22,25 The ZORA Fe electron densities are shifted towards the four-component Dirac–Fock limit, but no improvement in the correlation is observed.…”
Section: Introductionmentioning
confidence: 99%
“…They found the B3LYP and O3LYP density functionals to have the lowest errors while M06-2X and SVWN5 possess the highest for their large test set of 31 iron-containing complexes (35 signals), including both mononuclear and dinuclear systems. 26 …”
Section: Introductionmentioning
confidence: 99%